Age- and Sex-Specific Characteristics of Right Ventricular Compacted and Non-compacted Myocardium by Cardiac Magnetic Resonance - Kiss, Anna Réka; Gregor, Zsófia; Furák, Ádám; Szabó, Liliána Erzsébet; Dohy, Zsófia; Merkely, Béla; Vágó, Hajnalka; Szűcs, Andrea (Frontiers in Cardiovascular Medicine, 2021)
The age and sex-specific characteristics of right ventricular compacted (RV-CMi) and RV-trabeculated myocardial mass (RV-TMi) and the determinants of RV myocardium are less well studied; however, in different conditions, these might provide additional diagnostic information. We aimed to describe the age- and sex-specific characteristics of RV-CMi, RV-TMi, and RV volumetric and functional parameters and investigate the determinants of RV myocardial mass with cardiac magnetic resonance (CMR). Two hundred healthy Caucasian volunteers free of known cardiovascular or systemic diseases were prospectively enrolled in this study. Four different age groups were established with equal numbers of males and females: Group A (n=50, 20-29 years, mean age: 24.3±3.2 years), Group B (n=50, 30-39 years, mean age: 33.6±2.6 years), Group C (n=50, 40-49 years, mean age: 44.7±2.7 years), and Group D (n=50, ≥ 50 years, mean age: 55.1±3.9 years). Left ventricular (LV) and RV volumetric, functional, CMi, and TMi values were measured with a threshold-based post-processing CMR method. The volumetric parameters, RV-CMi, and RV-TMi values were larger, and the ejection fraction (EF) was lower in males. The RV-CMi did not correlate with age in either of the sexes, while the RV-TMi decreased with age in females but remained stable in males. The RV-TMi and RV-CMi correlated positively with RV volumetric parameters, the LV-CMi, the LV-TMi, and each other in both sexes. LV-TMi, LV-CMi, RV end-systolic volume, and sex were independent predictors of RV-TMi. Understanding the characteristics of RV-trabeculated and RV-compacted myocardium might have additive value in diagnosing different conditions with RV hypertrophy or hypertrabeculation.